Effects of rewards and pedometer-feedback on children's physical activity: a school-based intervention study - Allafi, Ahmad R (Progress in Nutrition, 2020)
Background: Current prevalence estimates for child obesity in Arabian Gulf countries are some ofthe world’s highest. The study aims to evaluate the effect of rewarding and pedometer- feedback on increasingthe children’s physical activity and decrease obesity rates. Methods: A sum of 225 participants (110 boys - 115girls) ranging from 9 to 11 years old from six public elementary schools in Kuwait City, Kuwait took part inthe study. Three different groups were created; feedback (FB), feedback with rewards (FD+R), and controlgroup (C). Children were assigned to one of the three groups randomly. In the FB group, participants receivedinformation about the function of pedometer only wherein the FB+R group received information about thefunction of the pedometer and were asked for a 3000 counts milestone to get ten stickers. The control groupparticipants haven’t received any information about the function of the pedometer. Pedometer counts weretaken from all participants through five physical education classes. Results: The average step counts for thegroups were; 2091±483 for the control group, 2655±577 for the FB group, and 3429±458 for the FB+R group.A significant difference was found in the counts among the three groups (p < 0.05). Post-hoc Tuky analysisindicated a specific significant difference between the FB+R group and the two other groups (P < 0.00). Conclusion: The results of the study showed that encouraging children with rewards will sustainably increase theirphysical activity.